Size‐Dependent Structural Alterations in Ag Nanoparticles during CO2 Electrolysis in a Gas‐Fed Zero‐Gap Electrolyzer. Issue 17 (8th September 2022) - Hu, Huifang; Liu, Menglong; Kong, Ying; Montiel, Iván Zelocualtecatl; Hou, Yuhui; Rudnev, Alexander V.; Broekmann, Peter
Abstract: Ag nanoparticles (NPs) are efficient electrocatalysts for electrochemical CO2 ‐to‐CO conversion. However, NPs are thermodynamically unstable and can undergo structural alterations under electrolysis operating conditions. These structural changes may play a crucial role in the deterioration of CO2 reduction reaction (CO2 RR) performance on the long‐term electrolysis time scale. Here, we studied the effect of NP size on NP degradation during CO2 RR. Polyvinylpyrrolidone‐capped 10, 40, and 100 nm Ag NPs deposited on a gas diffusion electrode were used as testbed catalysts in a gas‐fed zero‐gap electrolyzer. Inductively coupled plasma mass spectrometry indicated insignificant catalyst‐material detachment after galvanostatic CO2 electrolysis. Scanning electron microscopy analysis showed that smaller NPs tended to agglomerate during CO2 electrolysis. 100 nm NPs formed agglomerates consisting of only two‐three NPs and underwent pronounced fragmentation with the formation of particles several nanometers in size. The fragmentation was associated with cathodic corrosion of Ag NPs under conditions of intensive CO2 RR and hydrogen evolution. Abstract : Size effect : The exploration of catalyst structural changes during electrochemical CO2 conversion under harsh conditions (at current densities >0.2 A cm −2 ) is highly essential. This article studies the size effect on degradation behavior of Ag nanoparticle catalysts during CO2 electrolysis in a zero‐gap electrolyzer. Small nanoparticles tend to agglomerate, while 100 nm particles undergo pronounced fragmentation related to cathodic corrosion.